Zeitlich differenzierte Einzelkornerfassung bei der Siebklassierung mittels Radiofrequenz‐ Identifikation. Issue 6 (15th April 2014) - Kaufeld, Sebastian; Feil, Alexander; Pretz, Thomas; Peuker, Urs
<x xml:space="preserve">Abstract</x> In the field of sieve classification, high separation efficiencies are desirable. The aim of this article was to build a test unit in which the dwell time behavior of defined single grain fractions in a sieving process could continuously be measured. Transponders were fixated on reference blocks of defined geometrical dimensions and their release out of the sieve was detected via radio‐frequency identification (RFID). The results show the basic applicability of this method. Constrictions are to be seen in the large number of particles exiting the sieving unit, which leads to a reduction of the logging rate.